DEA (data envelopment analysis)-assisted supporting measures for ground coupled heat pumps implementing in Italy: A case study. (October 2015) - Longo, L.; Colantoni, A.; Castellucci, S.; Carlini, M.; Vecchione, L.; Savuto, E.; Pallozzi, V.; Di Carlo, A.; Bocci, E.; Moneti, M.; Cocchi, S.; Boubaker, K.
Abstract: Nowadays, the increasing of the energy consumption is producing serious global warming issues. Mainly most of greenhouse gas emissions in developed countries come from building equipments. In this context, GCHPs (ground coupled heat pumps) are candidate solution as air conditioning systems in buildings due to their higher efficiency compared to conventional devices. Actually, ground coupled heat pump systems are widely, recognized among the most efficient and comfortable used systems. Nevertheless, economic efficiency of the ground coupled heat pumps has to be proved. In this study, DEA (data envelopment analyses) method is applied to a real case in Italy. Highlights: Original investigation in terms of energy demands in buildings. Gathering conjoint classical and scientific analyses. Presenting original DEA (data envelopment analysis) economic optimization scheme analyses. Outlining economical feasibility of an efficient low enthalpy-geothermal plant with GCHP (ground coupled heat pump) exchangers.